Bound together: Social binding leads to faster processing, spatial distortion, and enhanced memory of interacting partners - Vestner, Tim; Tipper, Steven P; Hartley, Tom; Over, Harriet; Rueschemeyer, Shirley-Ann (Journal of experimental psychology. General, 2019)
The binding of features into perceptual wholes is a well-established phenomenon, which has previously only been studied in the context of early vision and low-level features, such as color or proximity. We hypothesized that a similar binding process, based on higher level information, could bind people into interacting groups, facilitating faster processing and enhanced memory of social situations. To investigate this possibility we used 3 experimental approaches to explore grouping effects in displays involving interacting people. First, using a visual search task we demonstrate more rapid processing for interacting (vs. noninteracting) pairs in an odd-quadrant paradigm (Experiments 1a and 1b). Second, using a spatial judgment task, we show that interacting individuals are remembered as physically closer than are noninteracting individuals (Experiments 2a and 2b). Finally, we show that memory retention of group-relevant and irrelevant features are enhanced when recalling interacting partners in a surprise memory task (Experiments 3a and 3b). Each of these results is consistent with the social binding hypothesis, and alternative explanations based on low level perceptual features and attentional effects are ruled out. We conclude that automatic midlevel grouping processes bind individuals into groups on the basis of their perceived interaction. Such social binding could provide the basis for more sophisticated social processing. Identifying the automatic encoding of social interactions in visual search, distortions of spatial working memory, and facilitated retrieval of object properties from longer-term memory, opens new approaches to studying social cognition with possible practical applications. (PsycINFO Database Record (c) 2019 APA, all rights reserved).